2020
DOI: 10.3390/metabo10010035
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Fungal Pathogens Responsible for Root Rot in American Ginseng

Abstract: Ginseng root is an economically valuable crop in Canada at high risk of yield loss caused by the pathogenic fungus Ilyonectria mors-panacis, formerly known as Cylindrocarpon destructans. While this pathogen has been well-characterized from morphological and genetic perspectives, little is known about the secondary metabolites it produces and their role in pathogenicity. We used an untargeted tandem liquid chromatography-mass spectrometry (LC-MS)-based approach paired with global natural products social molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Isolated fungi were cultured at three different medium, including MEA, PCA, and PDA, at 10, 20, and 30 day culture periods for natural Alternaria mycotoxin product investigation. Six plugs of each culture plate were extracted according to the method outlined by DesRochers et al Plugs of each culture strain were extracted with 3 mL of ethyl acetate by vortexing for 5 min. Then, samples were centrifuged at 10000 g , and the supernatant of each sample was transferred to another tube.…”
Section: Methodsmentioning
confidence: 99%
“…Isolated fungi were cultured at three different medium, including MEA, PCA, and PDA, at 10, 20, and 30 day culture periods for natural Alternaria mycotoxin product investigation. Six plugs of each culture plate were extracted according to the method outlined by DesRochers et al Plugs of each culture strain were extracted with 3 mL of ethyl acetate by vortexing for 5 min. Then, samples were centrifuged at 10000 g , and the supernatant of each sample was transferred to another tube.…”
Section: Methodsmentioning
confidence: 99%
“…However, for the American ginseng, previous studies have only focused on the ginsenoside content of the MR, and therefore, the systematic profiles of the total ginsenoside contents of other parts are unknown. Additionally, the American ginseng plant is susceptible to disease, invasion by insect pests, and harsh environment during its growth, which may lead to the development of abnormal characteristics, such as physical deformity caused by disease and discolouration [ 23 ]. Normally, these abnormal roots are discarded.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis showed that I. mors-panacis had the highest ratio in the diseased root endophyte samples ( Figure 3D ) corroborating with the findings of a previous study that presented I. mors-panacis as the main pathogen of P. notoginseng root rot ( Mi et al, 2017 ). I. mors-panacis is also the main pathogen of P. ginseng root rot ( Desrochers et al, 2020 ; Farh et al, 2020 ). P. lycopersici is also a plant fungal pathogen that causes severe root rot and root knot disease ( Errico et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%